Case Method-Based Learning in AUTOCAD-Assisted CAD Program Courses - Arisman Telaumbanua; Nurhasan Syah; Muhammad Giatman; Refdinal Refdinal; Oskah Dakhi (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research is to increase students' understanding of CAD program courses through the application of the case method learning model. This type of research is Classroom Action Research (CAR). This research was conducted to find solutions that can be done so that the potential of each teaching participant can be explored optimally. The subjects of this study were the fourth semester students of the Building Engineering Education Study Program, University of Nias, who at the time of this research were contracting 22 CAD courses. The method of measuring the level of success is carried out in three cycles. The method of data collection was carried out by observation, performance tests, quantitative and qualitative data collection, and data analysis techniques of learning implementation. Based on the results of data analysis and discussion, it was found that the most dominant activity of lecturers in providing lecture material using autocad media could increase student understanding by 0.47 points from cycle 1 to cycle 2 while the increase from cycle 2 to cycle 3 was 0.04 points. Activities in providing explanations to student questions using autocad media can increase student understanding by 0.25 points from cycle 1 to cycle 2 and increase student understanding by 0.27 points. The mastery of students' cognitive learning outcomes increased from cycles 1 to 3, with the percentage of mastery in cycle 1 being 31.82% and cycle 2 being 54.54%, and in cycle 3 being 90.9%. So it is concluded that the application of the case method learning model assisted by autocad media can improve students' understanding of the CAD program material.